2009 16th Working Conference on Reverse Engineering 2009
DOI: 10.1109/wcre.2009.50
|View full text |Cite
|
Sign up to set email alerts
|

Relating Identifier Naming Flaws and Code Quality: An Empirical Study

Abstract: Abstract-Studies have demonstrated the importance of good identifier names to program comprehension. It is unclear, however, whether poor naming has other effects that might impact maintenance effort, e.g. on code quality. We evaluated the quality of identifier names in 8 established open source Java applications libraries, using a set of 12 identifier naming guidelines. We found statistically significant associations between flawed identifiers (i.e. violating at least one guideline) and code quality issues re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 7 publications
1
55
0
1
Order By: Relevance
“…Source code is a common input for of traceability approaches [Antoniol et al(2002) Developers normally use identifiers [Butler et al(2009)Butler, Wermelinger, Yu, and Sharp] that are easy to remember. However, these identifiers possibly do not represent concepts in the source code and-or system domain.…”
Section: Source Codementioning
confidence: 99%
See 1 more Smart Citation
“…Source code is a common input for of traceability approaches [Antoniol et al(2002) Developers normally use identifiers [Butler et al(2009)Butler, Wermelinger, Yu, and Sharp] that are easy to remember. However, these identifiers possibly do not represent concepts in the source code and-or system domain.…”
Section: Source Codementioning
confidence: 99%
“…Software quality depends on identifiers' quality [Butler et al(2009) [Takang et al(1996)Takang, Grubb, and Macredie] compared abbreviated identifiers with full-word identifiers and uncommented code with commented code and empirically analysed the role played by identifiers and comments on source code understandability. They showed that (1) commented systems are more understandable than non-commented systems and, similarly, that (2) systems containing full-word identifiers are more understandable than those with abbreviated identifiers.…”
Section: Identifiers' Qualitymentioning
confidence: 99%
“…Butler et al [6] study the effect of identifier names on the quality of code. They find that identifiers that violate certain guidelines have lower code quality (more bug patterns) than ones that don't.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, naming conventions are crucial for improving the source code understandability. Butler et al [10] analyzed the impact of naming conventions on maintenance effort, i.e., on code quality. They evaluated the quality of identifiers in eight open-source Java libraries using 12 naming conventions.…”
Section: Identifiers and Program Comprehensionmentioning
confidence: 99%
“…However, we believe that fault proneness is a complex phenomenon hardly captured solely by structural characteristics of code entities. Indeed, several studies showed that identifiers impact program comprehension (e.g., [5], [6], [7], [8]) and code quality (e.g., [3], [9], [10]). We concur with Deißenböck and Pizka's observation that proper identifiers improve quality and that identifiers should be used consistently [6].…”
Section: Introductionmentioning
confidence: 99%